Konsep Pembelajaran Matematika di Kelas 1 Sekolah Dasar - I’zaati, Lailatul; Irawan, Wahyu Henky; Abdussakir, Abdussakir (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to describe the concept of mathematics learning at the elementary school level. The focus of this study is how the concept of mathematics learning at the elementary school level. This study uses a qualitative approach through the method used is library research for data collection. Data collection is carried out through books and literacy resources related to the concept of mathematics learning in elementary schools. The main source of articles comes from various journals indexed on google scholar. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The result of this study is that children at the elementary school level are children in the age range of 7-12 years old and are in the concrete operational stage where in this concrete operational stage children can understand logical operations that are reversible and conservation